Calibrating the system dynamics of LISA Pathfinder - Armano,M; Audley,H; Baird,J; Binetruy,P; Born,M; Bortoluzzi,D; Castelli,E; Cavalleri,A; Cesarini,A; Cruise,AM; Danzmann,K; de,Deus Silva M; et al. (Physical Review D, 2018)
LISA Pathfinder (LPF) was a European Space Agency mission with the aim to test key technologies for future space-borne gravitational-wave observatories like LISA. The main scientific goal of LPF was to demonstrate measurements of differential acceleration between free-falling test masses at the sub-femto-g level, and to understand the residual acceleration in terms of a physical model of stray forces, and displacement readout noise. A key step toward reaching the LPF goals was the correct calibration of the dynamics of LPF, which was a three-body system composed by two test-masses enclosed in a single spacecraft, and subject to control laws for system stability. In this work, we report on the calibration procedures adopted to calculate the residual differential stray force per unit mass acting on the two test-masses in their nominal positions. The physical parameters of the adopted dynamical model are presented, together with their role on LPF performance. The analysis and results of these experiments show that the dynamics of the system was accurately modeled and the dynamical parameters were stationary throughout the mission. Finally, the impact and importance of calibrating system dynamics for future space-based gravitational wave observatories is discussed.